702. Zinc Blockade of SOS Response Inhibits Horizontal Transfer of Antibiotic Resistance Genes in Enteric Bacteria. (26th November 2018) - Crane, John; Sutton, Mark; Cheema, Muhammad; Olyer, Michael
Abstract: Background: The SOS response is a conserved response to DNA damage that is found in Gram negative and Gram-positive bacteria. When DNA damage is sustained and severe, activation of error-prone DNA polymerases can induce a higher mutation rate then normally observed, which is called the mutator phenotype or hypermutation. We previously showed that zinc blocked the hypermutation response induced by quinolone antibiotics and mitomycin C in E. coli and Klebsiella pneumoniae (Bunnell BE, Escobar JF, Bair KL, Sutton MD, Crane JK (2017). Zinc blocks SOS-induced antibiotic resistance via inhibition of RecA in Escherichia coli. PLoS ONE 12(5): e0178303. https://doi.org/10.1371/journal.pone.0178303 .) In addition to causing copying errors in DNA replication, Beaber et al. showed that induction of the SOS response increased the frequency of horizontal gene transfer into Vibrio cholerae, an organism naturally competent at uptake of extracellular DNA. (Beaber JW, Hochhut B, Waldor MK. 2003. SOS response promotes horizontal dissemination of antibiotic resistance genes. Nature 427:72–74.) Methods. In this study, we tested whether induction of the SOS response could induce transfer of antibiotic resistance from Enterobacter cloacae into E. coli, and whether zinc could inhibit that inter-species transfer of antibiotic resistance. Results. Ciprofloxacin, an inducer of the SOS response, increased the rate of transfer of an extended spectrum β-lactamase (ESBL) gene from Enterobacter into a susceptible E. coli strain. Zinc blocked SOS-induced horizontal transfer of §-lactamase into E. coli . Other divalent metals, such as iron and manganese, failed to inhibit these responses. Conclusion. In vitro assays showed that zinc blocked the ability of RecA to bind to ssDNA, an early step in the SOS response, suggesting the mechanism by which zinc blocks the SOS response. Disclosures: All authors: No reported disclosures.